U.S. charter schools neglect promoting physical activity: Content analysis of nationally representative elementary charter school websites - David Kahan; Thomas L. McKenzie; Ashna Khatri (Preventive Medicine Reports, 2019)
Most youths fail to meet recommended public health recommendations for physical activity (PA) and schools have been assigned a key role in mitigating this problem. Charter school growth exploded recently, but little is known about these schools' support of PA. School websites offer public windows through which they can share information about their programs, policies, and values. Thus, during spring 2018, we completed a quantitative content analysis of specific information about PA on the websites of a representative sample of U.S. charter elementary schools (n = 759). Nearly all schools (97%) had a functioning website, but most (52%) did not mention even one of five PA programs frequently offered at schools: physical education (PE), recess, intramurals, interscholastics, and PA clubs. PE, a standard part of school curricula, was mentioned on only 34% of the sites. Although public health proponents identify schools as ideal locations for promoting PA, school websites are neglected both as a means for identifying the importance of PE and PA and as a vehicle for informing students about how and when to be active during the school day.